2021
DOI: 10.14814/phy2.15132
|View full text |Cite
|
Sign up to set email alerts
|

Application of oxygen saturation variability analysis for the detection of exacerbation in individuals with COPD: A proof‐of‐concept study

Abstract: Background Individuals with chronic obstructive pulmonary disease (COPD) commonly experience exacerbations, which may require hospital admission. Early detection of exacerbations, and therefore early treatment, could be crucial in preventing admission and improving outcomes. Our previous research has demonstrated that the pattern analysis of peripheral oxygen saturation (SpO2) fluctuations provides novel insights into the engagement of the respiratory control system in response to physiological stress (hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Intervention group showed significant variation from baseline for both heart rate and oxygen saturation pre-exacerbation. 88 randomised 44 to intervention 44 to control Nonin 3150 pulse oximeter 6 months or 1 st exacerbation Exacerbated N = 13; Male = 7 (54%) Mean age ± SD = 71 ± 3 Exacerbated N = 14; Male = 4(29%) Mean age ± SD = 72 ± 3 Composite score (of changes in heart rate and oxygen saturations) Composite score increased in control group for 1 day prior to exacerbation Composite score in intervention group increased for 7 days prior to exacerbation with a positive predictive value of 91.7%; sensitivity 84.6% and specificity of 81.8% FEV1% 52.9 Attrition rate: 52% Attrition rate: 59% Al Rajeh et al a 43 OBS Stable COPD patients Overnight pulse oximetry measurements (SpO2 and HR). Recorded every 4 seconds.…”
Section: Resultsmentioning
confidence: 98%
“…Intervention group showed significant variation from baseline for both heart rate and oxygen saturation pre-exacerbation. 88 randomised 44 to intervention 44 to control Nonin 3150 pulse oximeter 6 months or 1 st exacerbation Exacerbated N = 13; Male = 7 (54%) Mean age ± SD = 71 ± 3 Exacerbated N = 14; Male = 4(29%) Mean age ± SD = 72 ± 3 Composite score (of changes in heart rate and oxygen saturations) Composite score increased in control group for 1 day prior to exacerbation Composite score in intervention group increased for 7 days prior to exacerbation with a positive predictive value of 91.7%; sensitivity 84.6% and specificity of 81.8% FEV1% 52.9 Attrition rate: 52% Attrition rate: 59% Al Rajeh et al a 43 OBS Stable COPD patients Overnight pulse oximetry measurements (SpO2 and HR). Recorded every 4 seconds.…”
Section: Resultsmentioning
confidence: 98%
“…As hypothesis, we propose the coexistence of pathophysiological mechanisms in the decompensation of both diseases, with HR, Ox and their relationship serving as parameters that could represent a relevant common denominator for decompensation of both pathologies. Ox has already shown considerable utility in the detection of acute HF in previous studies 31 and has been considered the physiological parameter with the greatest discriminative power in COPD 10,32 . In addition, cutoff point of Ox for the detection of acute HF does not seem to be modi ed in patients who also have COPD 31 .…”
Section: Resultsmentioning
confidence: 99%
“…However, integration of such approaches into digital innovations may hold promise in the future. 75 Other examples of sensors include accelerometers which are small, portable, functionally diverse, and accurate. [76][77][78] A meta-analysis of 38 studies demonstrated that accelerometer-determined steps/day correlated with FEV1, and one study in 21 patients with COPD demonstrated an inverse correlation with hyperinflation.…”
Section: Supporting Recognition and Response To Copd Exacerbationsmentioning
confidence: 99%